One year after - Forstchen, William R. (Forge, 2015)
"Months before publication, William R. Forstchen's One Second After was cited on the floor of Congress as a book all Americans should read. Hundreds of thousands of people have read the tale. One Year After is the thrilling follow-up to that smash hit. The story picks up a year after One Second After ends, two years since the detonation of nuclear weapons above the United States brought America to its knees. After suffering starvation, war, and countless deaths, the survivors of Black Mountain, North Carolina, are beginning to piece back together the technologies they had once taken for granted: electricity, radio communications, and medications. They cling to the hope that a new national government is finally emerging. Then comes word that most of the young men and women of the community are to be drafted into an 'Army of National Recovery' and sent to trouble spots hundreds of miles away. When town administrator John Matherson protests the draft, he's offered a deal: leave Black Mountain and enter national service, and the draft will be reduced. But the brutal suppression of a neighboring community under its new federal administrator and the troops accompanying him suggests that all is not as it should be with this burgeoning government"--